Populizm religijno-polityczny Eva Moralesa wyzwaniem dla Kościoła katolickiego - Tomaszewski, Jarosław (Annales Missiologici Posnanienses, 2020)
The article shows the diffi cult problem of how to renew the dialogue between the Catholic Church, present in Bolivia since the sixteenth century and the populist regime of Evo Morales, nowadays expelled by the Bolivian opposition from his own country. The painful division of the Bolivian society into several distinctly separate groups is a huge missionary challenge for the Catholic Church in Bolivia. Catholicism cannot look indiff erently at the many social experiments conducted in the area of this very poor Andean country. What is required, is a radical change of the spiritual formation, which will lead effi ciently to a renewed reception of the Gospel in the free heart of the Bolivian nation.